Spatial Utilization of a Residential Building as a Cafe: A Case Study of Forester Coffee, Banda Aceh - Destri Wulanda; Alfikhairina Jamil; Putra Aulia Kesuma (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The utilization of residential buildings as commercial cafe spaces has become an increasingly prominent phenomenon in Indonesian urban contexts, reflecting shifting patterns of social interaction and the growing demand for experientially distinctive hospitality environments. This study examines the spatial utilization of Forester Coffee in Banda Aceh, a cafe operating within a former residential building, with the aim of analyzing how existing residential spaces accommodate cafe functions without substantial structural alteration. A qualitative research approach was employed, with data gathered through field observation, architectural documentation, and interviews with relevant parties. The analysis addresses eight spatial aspects: the creation of atmospheric diversity, the generation of a pleasant atmosphere, peaceful and structured spatial organization, acoustic comfort and visual tranquility, the introduction of new spatial interventions, spatial openness, simplicity and tranquility, and clarity of orientation within the adapted design. Findings indicate that the retention of residential spatial characteristics, encompassing domestic scale, natural element integration, and material authenticity, constitutes a significant design asset that enhances visitor comfort and strengthens the distinctive commercial identity of the establishment. This study contributes to scholarly understanding of residential building utilization within the hospitality and cafe sector.